Information Systems: In-House Development vs. Package Purchase - Espinoza Guido, Sergio (2011)
It’s not an easy task to know when and how to internally develop an application or to go for the purchase of a package that performs the same work, for a long timepeople involved in this process have discussed to determine which option is the best and most valid, this consuming and discouraging process has not been helpful at all, since both criteria are valid as long as the concepts to help you make the decision are applied.